Heterogeneous distributions in clinical events preceding anticoagulant treatment nonpersistence in patients with venous thromboembolism stratified by active cancer: A nationwide cohort study - Dongwon Yoon; Han Eol Jeong; Songhwa Choi; Daye Lee; Ju‐Young Shin; Soo‐Mee Bang (Cancer Medicine, 2023)
Abstract Background Nonpersistence in anticoagulation therapy is common and associated with undesirable clinical outcomes in patients with venous thromboembolism (VTE). Methods We investigated preceding clinical events of treatment nonpersistence (e.g., switching, discontinuing, or restarting) in VTE patients with and without active cancer using Korean claims database. Results Clinically significant events including thromboembolic events, hepatic function change and surgery preceded treatment nonpersistence, but heterogeneous distributions of clinical events were observed in the presence of active cancer. Patients with active cancer had a low rate of clinical events preceding treatment nonpersistence, and new active cancer diagnosis in the nonactive cancer group was most common before the switch to parenteral anticoagulants from warfarin or non‐vitamin K antagonist oral anticoagulants (NOACs). Conclusion These findings suggest that clinically significant events can precede treatment nonpersistence and largely paralleled current guidelines for patients with VTE, whereas heterogeneous distributions of clinical events were observed in the presence of active cancer.